Recommendations to enhance constructivist-based learning in Interprofessional Education using video-based self-assessment - Dahmen, Uta; Schulze, Christine; Schindler, Claudia; Wick, Katharina; Schwartze, Dominique; Veit, Andrea; Smolenski, Ulrich (GMS Journal for Medical Education, 2016)
Introduction: Interprofessional collaboration is crucial to the optimization of patient care.Aim: This paper aims to provide recommendations for implementing an innovative constructivist educational concept with the core element of video-based self-assessment.Methodology: A course for students in medicine, physiotherapy, and nursing was developed through interprofessional, cross-institutional collaboration. The course consisted of We evaluated the preparation and implementation of the three courses conducted thus far. Concrete recommendations for implementation were made based on evaluation sheets (students), open discussions (tutors, instructors, institutions) and recorded meeting minutes (project managers, project participants).Results: Basic recommendations for implementation include: selecting appropriate criteria for self-assessment and a simulated situation that offers members of each professional group an equal opportunity to act in the role play. In terms of administrative implementation we recommend early coordination among the professions and educational institutions regarding the target groups, scheduling and attendance policy to ensure participant recruitment across all professions. Procedural planning should include developing teaching materials, such as the case vignette and treatment scenario, and providing technical equipment that can be operated intuitively in order to ensure efficient recording.Conclusion: These recommendations serve as an aid for implementing an innovative constructivist educational concept with video-based self-assessment at its core.